(untitled) (Journal of Economic Research & Business Administration, 2015)
The higher education in the Republic of Kazakhstan started to develop in a new form since the state independence in 1991. The higher education system began to engage in rapid change from 1995 to 2005. In this period, the number of private schools rapidly grew and the competition condition among higher schools began to appear. The growing number of higher educational institutes began to influence education quality. A state control over the number of higher educational institutes was launched in 2005. Namely, United State Testing, midterm state monitoring and classifying students knowledge achievement. These means showed positive result in their senses. However, optimizing the number of higher educational institutes is still a vital issue nowadays. A state function aimed at solving this established situation is presented in this article.